2016
DOI: 10.1186/s12870-016-0937-7
|View full text |Cite
|
Sign up to set email alerts
|

Range-wide phenotypic and genetic differentiation in wild sunflower

Abstract: BackgroundDivergent phenotypes and genotypes are key signals for identifying the targets of natural selection in locally adapted populations. Here, we used a combination of common garden phenotyping for a variety of growth, plant architecture, and seed traits, along with single-nucleotide polymorphism (SNP) genotyping to characterize range-wide patterns of diversity in 15 populations of wild sunflower (Helianthus annuus L.) sampled along a latitudinal gradient in central North America. We analyzed geographic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…Nonetheless, we found a notable exception in sunflower, in which variation increases from that observed in the wild relatives. This exceptional case could be explained by the large phenotypic and genetic variation found in the continuum of landraces, hybrids, and genetically modified organisms that increases the phenotypic amplitude in the domesticated populations ( McAssey et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we found a notable exception in sunflower, in which variation increases from that observed in the wild relatives. This exceptional case could be explained by the large phenotypic and genetic variation found in the continuum of landraces, hybrids, and genetically modified organisms that increases the phenotypic amplitude in the domesticated populations ( McAssey et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In sunflower, only one of the association mapping studies so far was performed genome-wide ( Mandel et al, 2013 ), all others were candidate gene based ( Fusari et al, 2012 ; Cadic et al, 2013 ; Talukder et al, 2014b ; Nambeesan et al, 2015 ; McAssey et al, 2016 ). Genome-wide association mapping was performed in an association population of 271 lines ( Mandel et al, 2011 ), using 5,359 SNP marker from the Illumina Infinium Beadchip ( Mandel et al, 2013 ).…”
Section: Association Mappingmentioning
confidence: 99%
“…Most of these were found on LG10, where previous QTL mapping had detected the B-Locus for recessive branching ( Tang et al, 2006 ; Bachlava et al, 2009 ). With regard to flowering time, a SNP in HaFT2 was identified that co-localized with a flowering time QTL ( McAssey et al, 2016 ).…”
Section: Association Mappingmentioning
confidence: 99%
“…HA7-911263, found on LG 7, has similarity to an armadillo-type fold protein. McAssey et al (2016) previously observed a SNP outlier corresponding to an ARM repeat protein in H. annuus on the same LG (19.29 cM position), which colocalized with quantitative trait loci for flowering time, plant height, leaf number, and head herbivory in previous mapping studies (Burke et al, 2002;Dechaine et al, 2009). HA10-86839089 on LG 10 was annotated as similar to the known gene MALE GAMETOPHYTE DEFECTIVE 1 (MGP1-AT2G21870) in Arabidopsis, involved in the mitochondrial F1FO-ATP synthase necessary for viable pollen formation (Li et al, 2010).…”
Section: Candidate Gene Detectionmentioning
confidence: 77%